Observations on Working Psychoanalytically with a Profoundly Amnesic Patient - Moore, Paul A.; Salas, Christian E.; Dockree, Suvi; Turnbull, Oliver H. (Frontiers in Psychology, 2017)
Individuals with profound amnesia are markedly impaired in explicitly recalling new episodic events, but appear to preserve the capacity to use information from other sources. Amongst these preserved capacities is the ability to form new memories of an emotional nature – a skill at the heart of developing and sustaining interpersonal relationships. The psychoanalytic study of individuals with profound amnesia might contribute to the understanding the importance of each memory system, including effects on key analytic processes such as transference and countertransference. However, psychoanalytic work in the presence of profound amnesia might also require important technical modifications. In the first report of its kind, we describe observations from a long term psychoanalytic process [72 sessions] with an individual (JL) who has profound amnesia after an anoxic episode. The nature of therapy was shaped by JL’s impairment in connecting elements that belong to distant (and even relatively close) moments in the therapeutic process. However, we were also able to document areas of preservation, in what appears to be a functioning therapeutic alliance. As regards transference, the relationship between JL and his analyst can be viewed as the evolution of a narcissistic transference, and case material is provided that maps this into three phases: (i) rejecting; (ii) starting to take in; and (iii) full use of the analytic space – where each phase exhibits differing degrees of permeability between JL and the analyst. This investigation appears to have important theoretical implications for psychoanalytic practice, and for psychotherapy in general - and not only with regard to brain injured populations. We especially note that it raises questions concerning the mechanism of therapeutic action in psychoanalysis and psychotherapy, and the apparent unimportance of episodic memory for many elements of therapeutic change.